2022
DOI: 10.1093/advances/nmac074
|View full text |Cite
|
Sign up to set email alerts
|

Poultry Consumption and Human Health: How Much Is Really Known? A Systematically Searched Scoping Review and Research Perspective

Abstract: This scoping review was conducted to systematically search and chronicle scientific literature pertinent to poultry intake and human health. The protocol (uploaded to Open Science Framework, https://osf.io/2k7bj/) was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guidelines. Articles with observational and experimental research, narrative and systematic reviews, and meta-analyses were included. Among 13,141 articles identified, 525… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Since peach is not the most commonly eaten fruit, it can be argued that eating peaches represents a phenotype with high fruit intake, or even with a healthy lifestyle in general. The beneficial effects of poultry and nuts on healthy ageing were in line with previous studies [ 39–41 ]. The association between decelerated ageing and solid fats, such as butter and dairy-derived fats, that comprise primarily saturated fatty acids (SFAs), was rather unexpected.…”
Section: Discussionsupporting
confidence: 90%
“…Since peach is not the most commonly eaten fruit, it can be argued that eating peaches represents a phenotype with high fruit intake, or even with a healthy lifestyle in general. The beneficial effects of poultry and nuts on healthy ageing were in line with previous studies [ 39–41 ]. The association between decelerated ageing and solid fats, such as butter and dairy-derived fats, that comprise primarily saturated fatty acids (SFAs), was rather unexpected.…”
Section: Discussionsupporting
confidence: 90%
“…5,6 However, even the same proteins and fats can have significantly different amounts of saturated fatty acids and cholesterol per unit. [7][8][9][10][11] Moreover, the fat content in meats varies according to the anatomical part. 12 Ebbeling et al reported that the saturated fat content of the CRD/KD was 20%, which is significantly higher than that recommended by American and European guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of lipids are known to increase LDL‐C or TG levels 5,6 . However, even the same proteins and fats can have significantly different amounts of saturated fatty acids and cholesterol per unit 7–11 . Moreover, the fat content in meats varies according to the anatomical part 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, we published a systematically searched scoping review pertinent to poultry intake and all facets of human health [ 4 ]. Among 13,141 articles identified, 525 met inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Among 13,141 articles identified, 525 met inclusion criteria. Among these 525 articles, 41 were on cardiovascular disease (CVD) morbidity and mortality; 52 on CVD risk factors; 32 on type II diabetes mellitus (T2DM) morbidity and mortality; 33 on T2DM risk factors; and 42 on body weight and body composition [ 4 ]. This scoping review did not present results described in the articles.…”
Section: Introductionmentioning
confidence: 99%